2012
DOI: 10.1021/ma202127p
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mobility and Glass Transition of Thin Films of Poly(bisphenol A carbonate)

Abstract: Glass transition behavior of thin poly(bisphenol A carbonate) (PBAC) films capped between two aluminum (Al) layers is investigated by means of dielectric expansion dilatometry and dielectric relaxation spectroscopy accompanied by contact angle measurements. The thermal glass transition temperature is more or less independent of the film thickness down to 20 nm. For thickness below 20 nm, an increase of T g is observed. Meanwhile, an increase of the relaxation time at a fixed temperature is observed for the fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
113
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 90 publications
12
113
0
2
Order By: Relevance
“…The reliability of these investigations is demonstrated by comparing results obtained from two polymeric systems selected for their amorphous structure: polystyrene (PS), considered as a reference material because extensively studied by F-DSC, and poly(ethylene terephthalate)-glycol (PETg) which is much rarely studied by F-DSC techniques. In a second time, the temperature dependence of the cooling rate obtained by F-DSC and DSC combination has been compared to the temperature dependence of the relaxation times classically obtained from broadband dielectric spectroscopy, experiment considered as the reference concerning the fragility measurements [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The reliability of these investigations is demonstrated by comparing results obtained from two polymeric systems selected for their amorphous structure: polystyrene (PS), considered as a reference material because extensively studied by F-DSC, and poly(ethylene terephthalate)-glycol (PETg) which is much rarely studied by F-DSC techniques. In a second time, the temperature dependence of the cooling rate obtained by F-DSC and DSC combination has been compared to the temperature dependence of the relaxation times classically obtained from broadband dielectric spectroscopy, experiment considered as the reference concerning the fragility measurements [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Here we show how the interaction with the interface plays a dominant role in determining the direction and magnitude of T g deviations. Other studies point in the direction of reduced confinement effects once annealing well above T g for polymers exhibiting T g reduction [117,119,147,157,190]. However, in this case data are much more scarce and, therefore, we focus our attention on T g data.…”
Section: Free Interface and Out-of-equilibrium Dynamics In Confined Pmentioning
confidence: 99%
“…Among them we recall Al-capped polycarbonate (PC) [189], poly(ethylene terephthalate) (PET) [116] and poly(L-lactice) [107]. This is seen in numerous polymers.…”
Section: Equilibrium Dynamics Under Nanoscale Confinementmentioning
confidence: 99%
“…Besides, some other researchers reported that an attractive interaction between the polymer chains and substrate can lead to the reduction of chain mobility, thus precluding crystallization in the thin films . Napolitano and colleagues observed irreversible chain adsorption in ultrathin polymer films due to interfacial interaction . Jeong et al .…”
Section: Introductionmentioning
confidence: 99%